Advanced physico-chemical characterization of chitosan by means of TGA coupled on-line with FTIR and GCMS: Thermal degradation and water adsorption capacity - Corazzari, Ingrid; Nisticò, Roberto; Turci, Francesco; Faga, Maria Giulia; Franzoso, Flavia; Tabasso, Silvia; Magnacca, Giuliana (Polymer degradation and stability, 2015)
In this study, chitosan, a commercially-available linear polysaccharide mainly used as antibacterial agent, functional coating and drug-delivery system, is investigated to enlighten both water interactions and its thermal stability by using a set of complementary advanced thermal techniques, rarely applied in polysaccharides characterizations. DSC and TGA, here coupled with FTIR and GCMS analysis of the exhausted gas, were used to reveal thermal events and identify degradation products as a function of the temperature: three main steps in chitosan (N-deacetylation degree, DD = 78%) thermal degradation were highlighted and mechanism proposed. In order to make a comparison with other analogous polymeric systems and validate the results obtained, a medical grade chitosan (DD > 93%) and a commercial chitin were investigated too. Moreover, the water adsorption capacity of chitosan (DD = 78%) was followed by using thermo-microgravimetry (TMG) and the distinction between weight losses of both physically and chemically adsorbed water molecules was achieved. The approach followed allows a complete characterization of the thermal behaviors of the chitosan and highlights the need for complementary advanced thermal techniques in the detailed characterization of complex biopolymers.